2009
DOI: 10.1158/0008-5472.sabcs-09-5094
|View full text |Cite
|
Sign up to set email alerts
|

Safety of First-Line Letrozole Compared with Lapatinib Plus Letrozole in Patients with Postmenopausal Hormone Receptor Positive Metastatic Breast Cancer: EGF30008 Study.

Abstract: Background: EGF30008 was a double-blind, placebo-controlled phase III study which evaluated the benefit of adding lapatinib (L) to letrozole (Let) alone in patient (pts) with hormone receptor positive (HR+), metastatic breast cancer. Median progression-free survival (PFS) in pts with HER2+ tumors was significantly increased from 3 to 8.2 mos with dual therapy (HR [95% CI] =0.71 [0.53, 0.96], P=.019). Safety data presented at the 2008 San Antonio Breast Cancer Symposium demonstrated that the combination of L+Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These studies established trastuzumab as the first‐line treatment for HER2‐positive metastatic breast cancer. Similarly, for hormone receptor positive, HER2‐positive metastatic breast cancer, trastuzumab and an aromatase inhibitor are superior to an aromatase inhibitor alone, both in the first‐line and second‐line settings. Only one small study of an aromatase inhibitor with or without trastuzumab had confidence intervals that crossed unity (HR 0.67, CI 0.35–1.29) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies established trastuzumab as the first‐line treatment for HER2‐positive metastatic breast cancer. Similarly, for hormone receptor positive, HER2‐positive metastatic breast cancer, trastuzumab and an aromatase inhibitor are superior to an aromatase inhibitor alone, both in the first‐line and second‐line settings. Only one small study of an aromatase inhibitor with or without trastuzumab had confidence intervals that crossed unity (HR 0.67, CI 0.35–1.29) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serious adverse events related to the study drugs were reported in 8% of patients on combination therapy compared to 4% on letrozole/placebo, but of 16 fatalities reported as serious adverse events, only three -one patient on combination therapy and two patients on letrozole/placebo -were attributed to the study drugs. 35,36,41,42 Quality of life was assessed using the Functional Assessment of Cancer Therapy (FACT)-Breast and FACTGeneral survey tools. In the HER2+ subpopulation, quality of life scores were equivalent in the letrozole plus lapatinib and the letrozole plus placebo arms, demonstrating that improvement in PFS with combination therapy did not come at the expense of a significant decrement in quality …”
mentioning
confidence: 99%